Distribution of paired immunoglobulin-like receptor B in the nervous system related to regeneration difficulties after unilateral lumbar spinal cord injury - Wan-shu Peng (Neural Regeneration Research, 2015)
Paired immunoglobulin-like receptor B (PirB) is a functional receptor of myelin-associated inhibitors for axonal regeneration and synaptic plasticity in the central nervous system, and thus suppresses nerve regeneration. The regulatory effect of PirB on injured nerves has received a lot of attention. To better understand nerve regeneration inability after spinal cord injury, this study aimed to investigate the distribution of PirB (via immunofluorescence) in the central nervous system and peripheral nervous system 10 days after injury. Immunoreactivity for PirB increased in the dorsal root ganglia, sciatic nerves, and spinal cord segments. In the dorsal root ganglia and sciatic nerves, PirB was mainly distributed along neuronal and axonal membranes. PirB was found to exhibit a diffuse, intricate distribution in the dorsal and ventral regions. Immunoreactivity for PirB was enhanced in some cortical neurons located in the bilateral precentral gyri. Overall, the findings suggest a pattern of PirB immunoreactivity in the nervous system after unilateral spinal transection injury, and also indicate that PirB may suppress repair after injury.